The relationship between initial vitamin D levels and in vitro fertilization (IVF) outcomes in PCOS patients: a systematic review - Octavia, Leony; Andhika Panjarwanto, Dwi; Nabila, Putri; Geany, Putri Lenggo; Javier, R. Mohamad; Rahman, Aldo Aulia; Yora, Vallexa Septina; Sutanto, Lucky; Tandayu, Arthur Peter; Varsha, Srigita; Solichin, Sofyan (Frontiers in Medicine, 2025)
BackgroundPolycystic Ovary Syndrome (PCOS) is a common endocrine disorder affecting reproductive-age women and is often associated with infertility challenges. Recent studies suggest that vitamin D levels play a significant role in reproductive outcomes, particularly in PCOS patients undergoing in vitro fertilization (IVF).MethodsA systematic review was conducted following PRISMA guidelines. Studies published between 2014 and 2024 were analyzed, focusing on the impact of pre-treatment vitamin D levels on IVF outcomes such as fertilization rates, implantation rates, clinical pregnancy, and live birth rates. Only studies on PCOS-related infertility were included, while non-PCOS infertility cases were excluded.ResultThe review examined 59 studies, highlighting variations in outcomes based on study design and populations. Evidence generally supports the hypothesis that adequate vitamin D levels are associated with improved IVF success, though inconsistencies remain. Further research is recommended to standardize supplementation protocols and better understand vitamin D’s biological mechanisms in reproductive health.ConclusionThe relationship between initial vitamin D levels and in vitro fertilization (IVF) outcomes in women with polycystic ovary syndrome (PCOS) suggests that vitamin D plays a crucial role in enhancing IVF success, although the findings remain somewhat inconsistent. Research generally points to a positive correlation between higher baseline vitamin D levels and improved reproductive results, including increased live birth rates, pregnancy rates, and better ovarian responses during IVF treatments.Systematic review registrationCRD42024622381, https://www.crd.york.ac.uk/PROSPERO/view/CRD42024622381.